Culture and Normative Sociable Systems in a Period of Crisis: Issues of Theory and Practice - Yuzhina, Evgeniya; Zatsepa, Elizaveta (Slavica, 2022)
This article is devoted to the analysis of topical questions of the development of culture and normative sociable systems in a period of crisis. People faced new concept of reality in the third decade of 21st century. In the era of a brittle, anxious, nonlinear, incomprehensible world the question of responsibility for the state of culture and normative sociable systems is most acute. As representatives of culture, education and science, researchers can create the space of clean, healthy, favorable opportunities for  the development in the post crisis period.